Film Review: The Fruit Machine - Gouliquer, Lynne; Poulin, Carmen (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
The following is a review of The Fruit Machine documentary film directed by Sara Fodey. This documentary sheds light on a dark period in Canadian history. Using the testimonials of survivors and historical expert, The Fruit Machine film illustrates how a democratic state could legally wage a discriminatory campaign against its own citizens whose only crime was being (or suspected to be) “homosexual.” For fifty years, Canadian state institutions hunted down and interrogated thousands of individuals suspected of homosexuality. This film is a must see.